Endogamy Marriage Tradition Of Sayyid Community In Sidenre Village, Binamu District, Jeneponto Regency - Syamzan Syukur (Jurnal Adabiyah: Humanities and Islamic Studies, 2019)
This article tried to find out some questions below, first, the way of martial processions of endogamy marriage at Binamu District of Jeneponto District. Secondly, the social impact of endogamy marriage. Thirdly, what is the sanction of disobeying the rules of endogamy marriage?. This research was qualitative descriptive which means to explore the phenomenon of endogamy marriage at Binamu of Jeneponto District This article was tried to reveal whether or not Sayye' community in the Sidenre Subdistrict still maintained the tradition of endogamy marriage (The marriage between clans or kinship among them). Sayye’ women were named as syarifah or sayyidah who were prohibited marrying with men who were not Sayye’ because they cannot continue their clan. Whereas men are not given clan or kinship restrictions in conducting marital relations (patriarchal system). Sayyid community maintained this tradition as an attempt to maintain their clan which they believe that they had lineage from the Prophet Muhammad Saw. This tradition is certainly faced many problems among mellinea society. Nevertheless, this tradition still existed among Sayye' community. The marriage of this tradition is the impact on the limitation in choosing a marriage partner which effected many syarifah or sayyidah became spinster, it also showed that there are some prohibition and limitation of interacting with other people, especially in establishing interpersonal with other clans. The sanctions for those who do not obey this tradition are isolated from the community or broke down the cognation genetic relationships.